The Use of Precise Agriculture Technology in a Farm in Podlasie Region (Agricultural Engineering, 2016)
The article presents advantages resulting from implementation of the precise agriculture technology in a farm. The objective of the paper was to analyse devices used in precise agriculture on the example of the selected agricultural farm located in Podlaskie Voivodeship. Documentation of the farm and data included in the questionnaire of the survey carried out with the farm owner were the source of indispensable information. For determination of the costs of return of investments planned in the farm, the method of data analysis and TeeJeet calculation were used. Implementation of the precise agriculture technology in the investigated farm caused reduction of the costs related to running a farm. The introduced changes allowed saving approximately PLN 14 thousand annually on crop protection treatments and approximately PLN 19 thousand annually on the precise sowing of mineral fertilizers. Costs related to the purchase of devices which allow generation of such savings return after 3-4 years.